Diagnostic Potential Role of CXCL3 and Leptin Levels in Breast Cancer - Neamah, Abbas S.; Lafta, Fadhel Mohammed (Iraqi Journal of Science, 2024)
The risk of breast cancer development is believed to be attributed to the alterations of a number of key biological components. Within this context, elevated levels of some chemokines that act as growth factors and can promote cancer development. The current study was designed to evaluate CXCL3 (a chemokine C-X-C Motif Ligand 3) and leptin (a peptide hormone synthesized by adipose tissue with cytokine activity) serum of Iraqi breast cancer patients in comparison to healthy controls. A total of 90 participants consisted of 60 patients diagnosed with breast cancer and 30 healthy women as control group were enrolled into this case-control study. Venous blood samples were collected from all participants to evaluate CXCL3 and leptin serum levels using ELISA. The results demonstrated significantly (P≤0.001) higher mean levels of CXCL3 and leptin in breast cancer patients (1.19±0.10 ng/mL and 130.44± 3.72pg/mL) compared to those of their healthy counterparts (0.430± 0.02 g/mL and 57.1± 3.2pg/mL respectively). Interestingly, vast majority of the assessed breast cancer cases (up to 95-98%) showed to have elevated serum levels of both of the assessed potential biomarkers (CXCL3 and leptin). The present study results suggest an association of both CXCL3 and leptin in breast cancer pathogenicity. This supports the possibility of utilizing these potential biomarkers for breast cancer early detection and diagnosis.